High dose antithrombin supplementation in early preeclampsia: A randomized, double blind, placebo-controlled study. Issue 140 (April 2016) - D'Angelo, Armando; Valsecchi, Luca; ,
Abstract: Introduction: Antithrombin levels are often reduced in preeclampsia and infusion of antithrombin concentrates has been reported to prolong gestation in severe preeclampsia. We aimed to evaluate efficacy and safety of high-dose antithrombin (ATIII) supplementation in patients with single pregnancies and preeclampsia occurring before 30 weeks of gestation. Materials and methods: In November 2004 a double-blind, placebo-controlled trial (code KB033) was started in 13 Italian centers. The planned sample size was of 240 patients (intention-to-treat, ITT population) to detect a 30% relative risk reduction of the primary endpoint, composite perinatal morbidity. Eligible patients were randomized to high dose AT (3000 IU/daily, ATIII Kedrion S.p.A., Italy), or placebo (1% glycine) for 7 days or less until delivery, whichever came first. The per-protocol (PP) population was restricted to patients receiving at least two days of treatment. Results: The study was terminated by the sponsor in October 2007 after the enrolment of 38 evaluable patients – 20 randomized to high dose AT and 18 to placebo, 27 treated for 2 days or more – out of 164 screened patients. Enrolment failures were mainly represented by requirement for immediate delivery and consent refusal (91 patients). The primary endpoint occurred in 15 of 38 patients (39.5%), with a relative risk in the AT arm of 0.85 (95% CI 0.42–1.75) and 0.79 (95% CI 0.30-2.11) in the ITT and PP populations, respectively. Living neonates in the two arms had similar weight at birth, Apgar scores, and duration of hospitalization in neonatal ICU. In mothers, AT supplementation was associated with reduced blood loss at delivery and with surrogate laboratory markers (LDH, d -dimer). Conclusions: The results of this markedly underpowered trial, albeit suggestive of a potential maternal benefit, cannot support high-dose AT supplementation to improve fetal/neonatal outcomes in early preeclampsia. Highlights: Antithrombin (AT) supplementation in early preeclampsia was evaluated in a double-blind study. Planned sample size: 240 patients to detect a 30% RRR of composite perinatal morbidity. Study terminated after the enrolment, in 3 years, of 40 out of 164 potentially eligible patients. Enrolment failures were mainly due to immediate delivery and consent refusal. AT supplementation was safe but had no effect on the primary endpoint (underpowered analysis).